PENGARUH KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR SELATAN - Hermianti, Hermianti; Hakim, Lukman; Razak, Rosdianti (Universitas Muhammadiyah Makassar, 2022)
The purpose 0f this study was to find out how much influence service quality had on taxpayer compliance at the South Makassar Primary Tax Service Office. This study used quantitative. Data collection techniques used questionnaires and documentation. The data analysis technique used simple linear regression analysis. The data validation technique was obtained through validation tests reliability tests. The results of this study indicated that service quality had a positive and significant effect on taxpayer compliance at the South Makassar Primary Tax Service Office. Based on the output results of the summary model, it was positive because seen from the magnitude of the regression value of R Square was 0,280. So it could be concluded that the variable X (quality of service) had an influence of 28,0% on the variable Y (Taxpayer compliance) and the remaining 72,0% was influenced by other factors. Which meant that quality of service at the Makassar Primary Tax Service Office was quite good in increasing taxpayer compliance.